Employee service innovative behavior: The roles of leader-member exchange (LMX), work engagement, and job autonomy. Issue 2 (2nd May 2017) - Garg, Shreya; Dhar, Rajib
Abstract : Purpose: The purpose of this paper is to extend the under-researched work on service innovation by examining employee service innovative behavior in the Indian banking industry. In doing so, this study addresses the call for carrying out context-based research to advance service innovation literature. Design/methodology/approach: Using convenience sampling and self-administered survey methods, data were obtained from professionals employed in Indian public sector banks ( n =294). Findings: Findings reveal that leader-member exchange (LMX) shares a positive relationship with employee service innovative behavior via work engagement. Results also indicate that job autonomy as moderator strengthened the relationship between LMX and employee service innovative behavior mediated by work engagement. Practical implications: This study recommends that higher levels of LMX quality should be combined with enhanced levels of job autonomy for significantly influencing employee service innovative behavior. Originality/value: Even though previous studies on service innovation have produced a significant piece of work, this study is among the first to propose and analyze a comprehensive and theoretically grounded structure of LMX, work engagement, job autonomy and employee service innovative behavior by incorporating social exchange and job characteristics theories.